2002
DOI: 10.1074/jbc.m111392200
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus (HCV) NS5A Binds RNA-dependent RNA Polymerase (RdRP) NS5B and Modulates RNA-dependent RNA Polymerase Activity

Abstract: Hepatitis C virus (HCV) NS5B is RNA-dependent RNA polymerase (RdRP), the essential catalytic enzyme for HCV replication. Recently, NS5A has been reported to be important for the establishment of HCV replication in vitro by the adaptive mutations, although its role in viral replication remains uncertain. Here we report that purified bacterial recombinant NS5A and NS5B directly interact with each other in vitro, detected by glutathione S-transferase (GST) pull-down assay. Furthermore, complex formation of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
165
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(179 citation statements)
references
References 42 publications
11
165
0
3
Order By: Relevance
“…Previous reports have demonstrated that there is coassociation between NS5A and the other non-structural proteins (Dimitrova et al, 2003;Shirota et al, 2002). As the PSTCD system provided an ideal method to confirm this observation, lysates were prepared from naĂŻve Huh-7 cells or lines harbouring the FK5.1, FK5.1-PSTCD or FK5.1-DPSTCD replicons and biotinylated proteins were isolated from these cell lysates by using streptavidin-coated magnetic (SM) beads.…”
mentioning
confidence: 95%
“…Previous reports have demonstrated that there is coassociation between NS5A and the other non-structural proteins (Dimitrova et al, 2003;Shirota et al, 2002). As the PSTCD system provided an ideal method to confirm this observation, lysates were prepared from naĂŻve Huh-7 cells or lines harbouring the FK5.1, FK5.1-PSTCD or FK5.1-DPSTCD replicons and biotinylated proteins were isolated from these cell lysates by using streptavidin-coated magnetic (SM) beads.…”
mentioning
confidence: 95%
“…Even though recent evidence has indicated that NS5B associates with other HCV viral proteins, including NS3, NS4A, and NS5A (27,28), the direct influence of these proteins on the NS5B RdRp activity has been uncertain, with the exception that a recent report has indicated that NS5A modulates NS5B activity (28). NS3 possesses a serine protease domain in the NH 2 -terminal one-third of the protein and an NTPase/helicase domain that resides in the COOH-terminal 500 amino acid residues (5).…”
mentioning
confidence: 99%
“…It is still remained to be answered whether the NS3 helicase can unwind the heavily structured X-RNA at the 3'-end of the HCV genome and the double-stranded replication intermediate generated during HCV RNA replication to allow the NS5B to efficiently copy the RNA template in a cyclic manner. HCV NS5A, which can also form a complex with NS5B, was also tested in RdRp reaction, but it only slightly enhanced RNA synthesis efficiency (Shirota et al, 2002). These results all together suggest that individual HCV non-structural protein might not be sufficient for enabling NS5B to support cyclic replication.…”
Section: Discussionmentioning
confidence: 99%